Pharmacy Interventions and Laboratory Diagnostics in the Epidemiology of Neglected Tropical Infectious Diseases - Al Abbas, Yahya Salem; Al Haisi, Salem Hamed Mani; Al Almushaekh, Hassan Ibrahim Hassan; Alahmari, Hasel Mohammed Manea; Aljarah, Mukled Zaid Saeed; Alkhudaysh, Mohammed Nasser Mohammed; Al Fahhad, Nashmi Salem; Alotaibi, Muneer; Alshehri, Abdullah Ali Mohammed; Al muwallad, Taiba Ibrahim; Asiri, Huda Abdulrheem Mohammed; Ababsah, Emad Abdulatif; et al. (Journal of Ecohumanism, 2024)
Neglected tropical diseases (NTDs) comprise a diverse group of infectious diseases caused by bacteria, viruses, and parasites that predominantly affect impoverished populations in tropical and subtropical regions. Despite their significant impact on public health, NTDs have historically received less attention from both researchers and healthcare systems. Effective management of NTDs requires a coordinated, multidisciplinary approach that integrates pharmacy interventions and laboratory diagnostics. A diverse team of professionals—pharmacists, pharmacy technicians, epidemiological monitoring technicians, laboratory technicians, and phlebotomists—play critical roles in the control, treatment, and prevention of these diseases. Pharmacists contribute to patient care through medication dispensing, adherence monitoring, and pharmacovigilance, while pharmacy technicians assist with drug distribution and inventory management. Epidemiological monitoring technicians track disease trends, inform surveillance programs, and aid in the response to outbreaks. Laboratory technicians and phlebotomists provide the diagnostic foundation necessary for confirming infections and determining the appropriate treatment regimens. This review article examines the role of each healthcare professional in the epidemiology of NTDs, explores their collaboration in the control of these diseases, and highlights the challenges and opportunities in improving their impact on global health.